Penetrating Neck Injury: A Case Report and Review of Management - Varghese, Ashish (Springer-Verlag, 2012)
Penetrating neck injury constitutes 5–10 % of all cases seen in the emergency room. As surgeons we must be prepared to manage these cases. After stabilizing the general condition of the patient the neck injuries are assessed. Management has changed from routine exploration to selective exploration. Injury to aerodigestive tract and vessels are commonly seen.